2003
DOI: 10.2514/2.1968
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium Radio Frequency Discharge Plasma Effect on Conical Shock Wave: M = 2.5 Flow

Abstract: An experimental study of shock modi cation in an M = 2:5 supersonic ow of nonequilibrium plasma over a cone is discussed. The experiments are conducted in a nonequilibrium plasma supersonic wind tunnel. Recent experiments at the Ohio State University using a supersonic plasma ow over a quasi-two-dimensional wedge showed that an oblique shock can be considerably weakened by a transverse rf discharge plasma. The previously observed shock weakening, however, has been found consistent with a temperature rise in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…To this end, supersonic discharges for pumping such lasers have been reported in molecular flows using DC discharges [7−9], electron beam stabilization techniques [10], and a 13.56-MHz RF discharge [11]. Recent progress has been made at the Ohio State University also using a 13.56-MHz RF source to drive a volume-filling discharge in Mach 2.5 airflow [12]. Pulsed ionization schemes in conjunction with DC discharges have also been implemented successfully in subsonic flows to reduce arcing in CO 2 lasers.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, supersonic discharges for pumping such lasers have been reported in molecular flows using DC discharges [7−9], electron beam stabilization techniques [10], and a 13.56-MHz RF discharge [11]. Recent progress has been made at the Ohio State University also using a 13.56-MHz RF source to drive a volume-filling discharge in Mach 2.5 airflow [12]. Pulsed ionization schemes in conjunction with DC discharges have also been implemented successfully in subsonic flows to reduce arcing in CO 2 lasers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on thermal flow control includes energy addition using bulk heating of the flow by diffuse nonequilibrium plasmas [16][17][18][19][20][21], or localized heating by a plasma torch or by a pulsed laser breakdown [22][23][24][25][26][27]. Bulk heating of the flow to weaken the shock in a high-speed flow requires an extremely high plasma power budget (comparable with the flow enthalpy).…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that for a large part of the applied voltage values experimentally tested, the ionization degree of the plasma upstream the flat plate ranges between 10 -4 and 10 -3 . This range is much higher than the one estimated by [47] (1.2-3.0×10 -7 ), for which the shock wave modifications were attributed to only thermal effects.…”
Section: Electron Population Analysismentioning
confidence: 55%